Characterization and testing of the IceCube Upgrade mDOM ... - Mechbal, Sarah; Feigl, Nora; IceCube Collaboration (Deutsches Elektronen-Synchrotron, DESY, Hamburg, 2023)
38th International Cosmic Ray Conference, ICRC2023, Nagoya, Japan, 26 Jul 2023 - 3 Aug 2023; Proceedings of Science / International School for Advanced Studies (ICRC2023), 1183 (2023). doi:10.22323/1.444.1183 ... : In the 2025/26 South Pole field season, hundreds of new optical modules will be deployed in the deep central region of the IceCube array, as part of the IceCube Upgrade. 402 of these sensors are multi-PMT Digital Optical Modules (mDOMs), consisting of 24 3.1 inch photomultiplier tubes arranged inside a pressure vessel. mDOMs are currently being built and tested to ensure they satisfy the optical and environmental requirements to detect the Cherenkov radiation produced in interactions of high energy neutrinos in the deep glacial ice. We present results from the extensive acceptance testing each module undergoes. The verification program includes the characterisation of the detector’s week-long response in a dark and cold (sub-zero temperatures) environment, as well as the determination of essential optical performance parameters, using a pulsed external light source for linearity and transit time spread PMT measurements. ...